2018
DOI: 10.3847/1538-4357/aade9c
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of the Disk–Jet Coupling in the Broad-line Radio Quasar 4C+74.26

Abstract: Here we explore the disk-jet connection in the broad-line radio quasar 4C+74.26, utilizing the results of the multiwavelength monitoring of the source. The target is unique in that its radiative output at radio wavelengths is dominated by a moderately-beamed nuclear jet, at optical frequencies by the accretion disk, and in the hard X-ray range by the disk corona. Our analysis reveals a correlation (local and global significance of 96% and 98%, respectively) between the optical and radio bands, with the disk la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…However, the probability of observing such a close (milliparsec) system of binary SMBH might be too small [see 52]. But on the other hand, in the case of strong disk-jet connection [e.g., in 57] (see also [11]), the periodic modulations induced due to binary SMBH system could propagate down the jet affecting the Doppler boosted emission. In such case, true periodic timescales at the BH could be longer than the observed one due to relativistic effects, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the probability of observing such a close (milliparsec) system of binary SMBH might be too small [see 52]. But on the other hand, in the case of strong disk-jet connection [e.g., in 57] (see also [11]), the periodic modulations induced due to binary SMBH system could propagate down the jet affecting the Doppler boosted emission. In such case, true periodic timescales at the BH could be longer than the observed one due to relativistic effects, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…After we have employed three different methods to detect periodicity in the light curve, it should be pointed out that, in general, the statistical properties of blazar light curves can be characterized as red-noise processes that can potentially mimic a transient periodic behavior, especially in the low-frequency domain [see 11,14,42, for the discussion]. In addition, spurious peaks might arise owing to other sampling effects including discrete sampling, finite observation period and uneven sampling of the light curve.…”
Section: Significance Estimation and Monte Carlo Simulationmentioning
confidence: 99%
“…Hasenkopf et al (2002) reported a broad only line for the same ASCA, and also BeppoSAX data. In more recent work, a broad line was reported by Ballantyne & Fabian (2005); Ballantyne (2005); Larsson et al (2008);Patrick et al (2012);Tombesi et al (2014); Gofford et al (2013); Di Gesu & Costantini (2016); Lohfink et al (2017); Bhatta et al (2018). In contrast, Noda et al (2013) reported a narrow line only.…”
Section: Introductionmentioning
confidence: 92%
“…However, the fit is rather poor (χ 2 ν = 1.3, P null = 3 × 10 −4 ). Modifying the model setup by fixing R out = 1000 r g and disk inclination angle to 45 • (Bhatta et al 2018) only produced a poor best fit, with χ 2 ν = 1.5 and P null = 1 × 10 −8 . Modifying this model setup by relaxing the requirement for uniform emissivity leads to an improved fit (χ 2 ν = 1.2, P null = 0.01) with an inner disk emissivity index of 5 +2 −1 and an outer disk index of 0.8 +0.5 −1.1 for an assumed break radius of 20 r g .…”
Section: Fe Kα Emission Linementioning
confidence: 99%
See 1 more Smart Citation